THE INFLUENCE OF BRAND IMAGE TOWARDS TOYOTA AGYA CAR PURCHASE DECISION AT PT. HADJI KALLA GOWA BRANCH, GOWA REGENCY - Buyung, Buyung; Aswar, Aswar; Trisdayanti, Andi Trisdayanti (Perpustakaan dan Penerbitan Unismuh Makassar, 2018)
The purpose of this study was to determine how much influence the Brand Image of Toyota Agya Car Purchasing Decision Making at PT. HADJI KALLA GOWA Branch GOWA Regency. The method used in this study is a simple regression method to see the effect of brand image on decision making of Toyota Agya Car Purchases and use the correlation coefficient to see how much influence the brand image of Toyota Agya Car Purchase Decision Making at PT. HADJI KALLA GOWA Branch in Gowa Regency. Based on the results of the analysis note that the influence of the Brand Image of Toyota Agya Car Purchasing Decision Making is relatively strong, seen from the value of r = 0.991. In addition, based on the results of the calculation of the correlation coefficient shows the value of r square = 0.982 shows that as much as 98% of Toyota Agya's car purchase decision-making is influenced by Brand Image. While the remaining 2% is influenced by other factors not examined.